Conventional and Novel Technologies in the Production of Dairy Bioactive Peptides - Murtaza, Mian Anjum; Irfan, Shafeeqa; Hafiz, Iram; Ranjha, Muhammad Modassar A. N.; Rahaman, Abdul; Murtaza, Mian Shamas; Ibrahim, Salam A.; Siddiqui, Shahida Anusha (Frontiers in Nutrition, 2022)
Background: In recent years, researchers have focused on functional ingredients, functional foods, and nutraceuticals due to the rapidly increasing interest in bioactive components, especially in bioactive peptides. Dairy proteins are a rich and balanced source of amino acids and their derived bioactive peptides, which possess biological and physiological properties. In the dairy industry, microbial fermentation and enzymatic hydrolysis are promising methods for producing bioactive peptides because of their rapid efficiency, and mild reaction conditions. However, these methods utilize less raw material, take long reaction time, result in low yields and low activity products, which pose industry to seek for alternative novel methods. Scope and approach: This review emphasizes the availability of peptides in dairy proteins and discussing the potential use of novel technologies in context to conventional methods of bioactive peptides production from dairy proteins, including the mechanisms along with their respective examples of use, advantages, limitations, and challenges to each technology. Key findings and conclusions: Noteworthily, hydrolysis of dairy proteins liberate inclusive peptides that possess remarkable biological functions to maintain human health. Novel technologies in the dairy industry such as UAE, MAE, and HPP are sustainable, innovative, environmentally friendly, and promising pretreatments to modify peptides’ profile, improve the yields, and high liberation of bioactive peptides as compared to conventional processing technologies. UAE is an innovative and most efficient technology as its mechanical effects and cavitation change the protein conformation, increase the biological functionalities of enzymes, and enhance enzymatic hydrolysis reaction rate.